Galectin‐1 Prolongs Survival of Mouse Liver Allografts From Flt3L‐Pretreated Donors. Issue 3 (28th January 2013) - Ye, Y.; Yan, S.; Jiang, G.; Zhou, L.; Xie, H.; Xie, X.; Yu, X.; Ding, Y.; Tian, J.; Dai, Y.; Zheng, S.
<x xml:space="preserve">Abstract</x> Liver allografts are spontaneously accepted across MHC barriers in mice. The mechanisms underlying this phenomenon remain poorly understood. Galectin‐1, an endogenous lectin expressed in lymphoid organs, plays a vital role in maintaining central and peripheral tolerance. This study was to investigate the role of galectin‐1 in spontaneous tolerance of liver allografts in mice, and to evaluate the therapeutic effects of galectin‐1 on liver allograft rejection induced by donor Flt3L pretreatment. Blockade of the galectin‐1 pathway via neutralizing antigalectin‐1 mAb did not affect survival of the liver allografts from B6 donors into C3H recipients. Administration of rGal‐1 significantly prolonged survival of liver allografts from Flt3L‐pretreated donors and ameliorated Flt3L‐triggered liver allograft rejection. This effect was associated with increased apoptosis of T cells in both allografts and spleens, decreased frequencies of Th1 and Th17 cells, decreased expression of Th1‐associated cytokines (IL‐12, IL‐2 and IFN‐γ), Th17‐associated cytokines (IL‐23 and IL‐17) and granzyme B, in parallel with selectively increased IL‐10 expression in liver allografts. In vitro, galectin‐1 inhibited Flt3L‐differentiated DC‐mediated proliferation of allo‐CD4+ T cells and production of IFN‐γ and IL‐17. These data provide new evidence of the potential regulatory effects of galectin‐1 in alloimmune responses in a murine model of liver transplantation.